2022
DOI: 10.1002/jper.21-0477
|View full text |Cite
|
Sign up to set email alerts
|

Patients with periodontitis and erectile dysfunction suffer a greater incidence of major adverse cardiovascular events: A prospective study in a Spanish population

Abstract: Background: Periodontitis and erectile dysfunction (ED) have been linked with cardiovascular disease. The association of periodontitis and ED with the occurrence of major adverse cardiovascular events has not been previously assessed.The aim of this study was to determine if the presence of periodontitis and ED has any effect on the incidence of major adverse cardiovascular events.Methods: Male patients that attended the Urology service were enrolled in a prospective study. Erectile dysfunction was diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Based on prior investigations, erectile dysfunction is thought to be an early indicator of endothelial impairment. This also implies that its pathophysiological pathways may overlap with those involved in the development of certain cardiovascular diseases and that the presence of erectile dysfunction may raise the chance of developing cardiovascular diseases [20][21][22][23]. Therefore, a unified view of cardiovascular disease and erectile dysfunction helps us to better understand erectile dysfunction.…”
Section: Plos Onementioning
confidence: 99%
“…Based on prior investigations, erectile dysfunction is thought to be an early indicator of endothelial impairment. This also implies that its pathophysiological pathways may overlap with those involved in the development of certain cardiovascular diseases and that the presence of erectile dysfunction may raise the chance of developing cardiovascular diseases [20][21][22][23]. Therefore, a unified view of cardiovascular disease and erectile dysfunction helps us to better understand erectile dysfunction.…”
Section: Plos Onementioning
confidence: 99%
“…Recently, a study evaluated the prevalence of periodontitis in patients with ED, observing that patients with ED showed a greater extent of moderate or severe chronic periodontitis than the control group [ 147 ]. A prospective study, also conducted by the same research group, observed that patients with periodontitis and ED showed a 3.7-fold increased risk of suffering major cardiovascular adverse events after a mean follow-up of 4.2 years [ 148 ]. In conclusion, the literature review suggests that preventive actions against periodontal disease in both men and women are justified in order to avoid problems such as infertility and preterm birth.…”
Section: Periodontal Health and Disease Infertility And Adverse Pregn...mentioning
confidence: 99%
“…However, a higher risk of heart disease (RR: 2.58, 95% CI: 2.20–.03) and cerebrovascular diseases (RR: 3.11, 95% CI: 2.42–3.98) were detected ( 126 ). Likewise, patients with periodontitis and erectile dysfunction presented a higher number of cardiovascular adverse events adjusted by age and previous cardiovascular disease ( 127 ).…”
Section: Association Of Periodontitis With Cvdsmentioning
confidence: 99%